Design of a current mode PI controller for a single-phase PWM inverter - Cherati, S. M. (IEEE Explorer, 2011)
This paper presents the design of current mode PI controller for single-phase PWM inverter. The controller is comprised of inductor current as the inner loop and output voltage as the outer feedback loop. The control design is carried out using Sisotool, which is provided in Matlab. By using this tool, users can examine the effects of changing the gain control values to system's transient response and stability, simultaneously. Hence, simplify and speed up the control design process. To evaluate the performance of the designed controller, the inverter is simulated under several types of load disturbances. From the result, it is shown that the designed controller exhibits a good transient response i.e. fast rising and settling time with small overshoot when subjected to step load disturbance.